1992
DOI: 10.1099/0022-1317-73-5-1317
|View full text |Cite
|
Sign up to set email alerts
|

A comparison, using dsRNA analysis, between beet soil-borne virus and some other tubular viruses isolated from sugar beet

Abstract: Double-stranded RNA preparations from Chenopodium quinoa leaves inoculated with two English isolates of beet soil-borne virus (BSBV), BSBV-N and BSBV-452N, a French isolate of beet necrotic yellow vein virus (BNYVV), a Swedish isolate of a tubular beet virus (86-109) or a Belgian isolate of a similar virus (1530) were compared following separation on non-denaturing polyacrylamide gels. The dsRNAs of BNYVV differed in mobility from those isolated from tissue infected with the other four tubular beet viruses, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The dsRNA profile detected in this study was same as previously reported BNYVV dsRNA profiles (Hutchinson et al, 1992;Ilhan & Ertunç, 2001;Ertunç & Ilhan, 2002). Non-specific bands were observed in agarose gel.…”
Section: Resultssupporting
confidence: 90%
“…The dsRNA profile detected in this study was same as previously reported BNYVV dsRNA profiles (Hutchinson et al, 1992;Ilhan & Ertunç, 2001;Ertunç & Ilhan, 2002). Non-specific bands were observed in agarose gel.…”
Section: Resultssupporting
confidence: 90%
“…Southern blotting of RT-PCR products using HyBond N + (Amersham) was carried out according to the n:anufacturer\s instructions and wa,shcd under conditions of high stringency. All other procedures were as described in Sambrook et al, (1989) except for the radio-labelling of dRNAs with [32P] ATP which was carried out as described by Hutchinson et al, (1992),…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr) Ampmentioning
confidence: 99%
“…The multipartite singlestranded RNA genome of BNYVV consists of four RNA species referred to as RNA 1-4, and a fifth RNA species (RNA5) is found in some isolates [1][2][3][4]. Other soilborne sugarbeet viruses include Beet soilborne mosaic virus (BSBMV), also a member of genus Benyvirus [5], and Beet soilborne virus (BSBV) and Beet virus Q (BVQ) that belong to genus Pomovirus and have multipartite genomes consisting of three RNA species [6,7]. All these viruses belong to family Tubiviridae and have their coat protein (CP) gene located on RNA2 [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%